2020
DOI: 10.1109/access.2020.3012618
|View full text |Cite
|
Sign up to set email alerts
|

Improving Urban Traffic Throughput With Vehicle Platooning: Theory and Experiments

Abstract: In this paper we present a model-predictive control (MPC) based approach for vehicle platooning in an urban traffic setting. Our primary goal is to demonstrate that vehicle platooning has the potential to significantly increase throughput at intersections, which can create bottlenecks in the traffic flow. To do so, our approach relies on vehicle connectivity: vehicle-to-vehicle (V2V) and vehicle-toinfrastructure (V2I) communication. In particular, we introduce a customized V2V message set which features a velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…For Eco-CACC-U control, many researchers have taken a systematic approach to test and evaluate that particular technology (38)(39)(40)(41). Lammert et al evaluated fuel consumption results of two Class 8 tractor-trailer combinations platooned together compared with their stand-alone fuel consumption (42).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For Eco-CACC-U control, many researchers have taken a systematic approach to test and evaluate that particular technology (38)(39)(40)(41). Lammert et al evaluated fuel consumption results of two Class 8 tractor-trailer combinations platooned together compared with their stand-alone fuel consumption (42).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They tested various speeds, distance gaps, and the mass of the vehicles to determine the best combination leading to the lowest fuel consumption. Smith et al developed a model-predictive control-based approach for vehicle platooning in an urban traffic setting ( 38 ). Their study involved experiments performed with real test vehicles on a closed track and demonstrated that vehicle platooning has the potential to increase throughput significantly at intersections.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar with [37], we consider that a platoon is deemed to pass the stop line if the leader vehicle of the platoon passes the stop line. Thus, V k,1 first observes the remaining time of green light and then estimates whether it can accelerate with the maximum acceleration a specified in [26] to ensure it passes the stop line before the due time of the green light [37].…”
Section: B) Green Lightmentioning
confidence: 99%
“…Similar with [37], we consider that a platoon is deemed to pass the stop line if the leader vehicle of the platoon passes the stop line. Thus, V k,1 first observes the remaining time of green light and then estimates whether it can accelerate with the maximum acceleration a specified in [26] to ensure it passes the stop line before the due time of the green light [37]. If V k,1 can pass the stop line, V k,1 makes a uniform acceleration linear motion with acceleration a until it passes the stop line; Otherwise, it reduces its acceleration in real time, similar to its operation under the red light.…”
Section: B) Green Lightmentioning
confidence: 99%
“…Automated and connected mobility is currently forecasted reshaping public and private transportation over the next few decades [1][2][3][4]. Remarkable benefits could be achieved in general through implementing automated mobility, including enhancing passenger comfort, reducing energy consumption for propulsion, enhancing traffic management, and improving road safety, among others [5]. This technological advance demands developing effective and flexible numerical tools for controlling and designing automated vehicles [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%